2019
DOI: 10.24052/jbrmr/v13is03/art-17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using balanced scorecard (BSC) on reducing production costs in the Jordanian industrial companies

Abstract: The study aims to measure the effect of using balanced scorecard (BSC); with its different perspectives on reducing production costs in the Jordanian industrial companies. The study depends on the questionnaire which was addressed to the financial managers, accounting department heads, managerial and costs accountants. The study sample contained (171) employees working in the Jordanian industrial companies. It used the descriptive, analytical, and also the regression analysis methods. The study results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Data were collected from the yearly reports of all Jordanian industrial companies listed in Amman Stock Exchange (ASE) during the period (2014-2018) (www.ase.com.jo/2019), and these companies represented a clear society for this study, where this sector was selected due to its significance in supporting the Jordanian economy (Bataineh, 2018), and the number of listed companies in this sector amounted to (52) companies by the end of (2018).…”
Section: Sample Characteristics and Data Collectionmentioning
confidence: 99%
“…Data were collected from the yearly reports of all Jordanian industrial companies listed in Amman Stock Exchange (ASE) during the period (2014-2018) (www.ase.com.jo/2019), and these companies represented a clear society for this study, where this sector was selected due to its significance in supporting the Jordanian economy (Bataineh, 2018), and the number of listed companies in this sector amounted to (52) companies by the end of (2018).…”
Section: Sample Characteristics and Data Collectionmentioning
confidence: 99%
“…In recent years, Bataineh (2018) showed that the use of IT can reduce the labor time, thereby decreasing the overall costs.…”
Section: 1mentioning
confidence: 99%
“…Businesses reap importance by adopting E-accounting such as saving time, effort, cost, and this would contribute to improving the performance of these Businesses and strengthening their competitive position in the market, in addition to support cash flows and profitability (Bataineh, 2018;Elessa et al, 2023). Is it possible for Businesses to survive without adopting the E-Accounting?…”
Section: Introductionmentioning
confidence: 99%